(untitled) (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2026)
The selection of the Exemplary Religious Affairs Office (KUA) in Muaro Jambi Regency is currently hindered by manual, subjective assessments that lack transparency and objective benchmarking. This study addresses this gap by developing a web-based Decision Support System (DSS) that integrates Simple Additive Weighting (SAW) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). Developed using the waterfall model, the system aims to enhance objectivity and efficiency in evaluating institutional performance. The primary scientific contribution lies in the proposed hybrid Multi-Criteria Decision-Making (MCDM) architecture: SAW is utilized to establish transparent initial criteria weights, which are then processed through TOPSIS to resolve complex trade-offs by identifying the shortest distance to the positive ideal solution. Results indicate that this integrated framework significantly improves ranking consistency and provides a robust validation mechanism compared to traditional manual evaluations. Beyond its practical application, this study contributes to the theoretical discourse on hybrid MCDM integration, offering a validated framework for enhancing accountability and objective governance within public sector institutional evaluations.